Contribuições da tecnologia BIM na utilização de estratégias autorregulatórias por estudantes de arquitetura e urbanismo. - Corrêa, Luciano de Vasconcellos (2019)
This thesis is a research in the field of education about contributions of the implementation of Building Information Modeling (BIM) technology in light of the Self- Regulatory Learning construct, with which I intend to contribute to the architecture and urbanism scholars mobilize strategies to become more autonomous and capable in relation to their learning. Thus, this research aims to understand how BIM technology constitutes a resource for the development of strategies and motivation for selfregulation of the learning. Having contextualized the motivations and thematic, I present the problem of thesis: can the modeling of the architectural object in a BIM technology software contribute to the development of self-regulatory strategies by undergraduate students of architecture and urbanism? It is a qualitative research with emphasis on the case study methodology, conducted with more than one hundred students of the architecture course of the Universidade Federal Pelotas (UFPel). The case study encompasses students' contextual reality, self-regulating learning strategies, self-regulating motivation used to learn BIM technology. The resources used for data collection focused on implementing BIM technology as a resource for the development of strategies and motivation for self-regulation of the learning of architecture and urbanism students. The collected data were submited to content analysis technique and two categories emerged from it: a) the potentialities of the use of BIM technology, specifically in the use of a modeling tool, and b) the contributions of BIM technology in the use of self-regulatory strategies by students of architecture. The findings of this research reveal that the students of Architecture and Urbanism use various self-regulatory strategies to implement BIM technology. Among the most cited are time control and self-registration. It was also noticed that the motivational approach guided students' interest in the use of BIM technology and stimulated the transformation for the realization of architectural projects. In view of the obtained results from the analysis of the stages of this study, the thesis that is defended is that BIM technology and its use in the academic environment brought contributions to the students, because when using self-regulatory strategies, they were able to implement the planning more effectively. execution and self-reflection about the projects carried out. This cyclical control allows the students to resize and change the ways of behaving, acting in a collaborative context such as those developed in the work stages of this research.